Controversies in Cardiology. Part 1. Should I treat a high risk chronic coronary syndrome invasively from the beginning? yes, in most cases - Ortiz Zegarra, César Antonio (2020)
Chronic coronary syndrome (SCC) previously known as stable coronary disease, is the main cause of mortality in the world, and it is one of the most important in Peru. This pathology has a dynamic nature that results in different clinical scenarios that can be modified through various therapeutic options, one of which is coronary interventional treatment, mainly in patients with high ischemic risk defined as ischemia greater than 10% of the entire left ventricular mass. For this reason, we have analyzed the most relevant and current information available, concluding that the treatment of high ischemic risk´s chronic coronary syndrome, after an individual evaluation, would correspond to an invasive management from the beginning, although it would not impact on mortality or cardiovascular events, it would contribute to improve quality of life; also we should consider the incomplete availability of all the therapeutic options for the symptomatic management of this disease, the limited access to the management of acute cardiovascular events in our country, as well as the risk of adverse effects and drug interactions.